Public Information Control Strategy to Increase Positive Perception of Investors in Central Java - Budi Sihabudin; Dian Purnamasari Abidin; Yani Nurhayani (ijd-demos, 2026)
Abstract Public information control strategies that can enhance positive investor perceptions in Central Java. Investor perceptions of a region are crucial in determining their investment decisions. Disseminated public information can influence investor perceptions, both positively and negatively. Therefore, an effective public information control strategy is needed to strengthen positive perceptions and encourage investment in Central Java. This research used qualitative and literature-based methods, involving interviews with stakeholders in Central Java. The results indicate that positive investor perceptions of the Central Java Provincial Government are formed through a combination of factors: maintained political stability, adequate infrastructure development, ease of licensing and investment services, government transparency and accountability, diverse regional economic potential, competitive human resource quality, and effective communication and public information provision. These factors contribute to creating a conducive investment climate and increasing investor confidence in investing in Central Java Province. Keywords: public information control strategies, positive perceptions, investors, Central Java.